A Mobile, Electronic Health Record-Connected Application for Managing Team Workflows in Inpatient Care - Soegaard Ballester, Jacqueline M.; Bass, Geoffrey D.; Urbani, Richard; Fala, Glenn; Patel, Rutvij; Leri, Damien; Steinkamp, Jackson M.; Denson, Joshua L.; Rosin, Roy; Adusumalli, Srinath; Hanson, Clarence William; Koppel, Ross; Airan-Javia, Subha (Applied Clinical Informatics, 2021)
Background Clinical workflows require the ability to synthesize and act on existing and emerging patient information. While offering multiple benefits, in many circumstances electronic health records (EHRs) do not adequately support these needs.Objectives We sought to design, build, and implement an EHR-connected rounding and handoff tool with real-time data that supports care plan organization and team-based care. This article first describes our process, from ideation and development through implementation; and second, the research findings of objective use, efficacy, and efficiency, along with qualitative assessments of user experience.Methods Guided by user-centered design and Agile development methodologies, our interdisciplinary team designed and built Carelign as a responsive web application, accessible from any mobile or desktop device, that gathers and integrates data from a health care institution's information systems. Implementation and iterative improvements spanned January to July 2016. We assessed acceptance via usage metrics, user observations, time–motion studies, and user surveys.Results By July 2016, Carelign was implemented on 152 of 169 total inpatient services across three hospitals staffing 1,616 hospital beds. Acceptance was near-immediate: in July 2016, 3,275 average unique weekly users generated 26,981 average weekly access sessions; these metrics remained steady over the following 4 years. In 2016 and 2018 surveys, users positively rated Carelign's workflow integration, support of clinical activities, and overall impact on work life.Conclusion User-focused design, multidisciplinary development teams, and rapid iteration enabled creation, adoption, and sustained use of a patient-centered digital workflow tool that supports diverse users' and teams' evolving care plan organization needs.
Keywords: mobile application; workflows; user-centered design; handoffs